The role of sentiment in the provision of credit - Björn O. Meyer (Kiel Institute for the World Economy (IfW), 2014)
The provision of credit has been shown to be eminent for macroeconomic activity. Recent research highlighted that optimism may play a role in the provision of credit through leverage cycles. A decomposition of corporate bond spreads allows the modelling of a propensity-to-lend through an excess bond premium. In the US economy, optimism in various sentiment measures causes within a VAR model, including other financial market variables, a fall of this excess bond premium and therefore increase the propensity-to-lend. Use of the Michigan Consumer Sentiment Index and animal spirit indices show a variation of information content in sentiment and different types of animal spirits. The overall reaction to positive animal spirits seems to be dominated by a positive response of the credit provision and its subsequent reversal, while an increase in the MCSI causes a more persistent positive response.
Keywords: E03; E22; E32; E44; 330